Generation of non-classical light via selfinduced transparency in mercury-filled hollow core photonic crystal fibers - Vogl, Ulrich; Sedlmeir, Florian; Joly, Nicolas Y.; Marquardt, Christoph; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2016)
We successfully demonstrate squeezing of nanosecond pulses via self-induced transparency in a system of mercury vapor confined in a hollow core kagomé-style fiber.
CRIS-Team Scopus Importer:2022-06-05